The Effect of Covenant Debt And Managerial Ownership On Accounting Conservatism - Suryo Nugroho (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2022)
The emergence of the trend of weakening the value of the rupiah is considered to have a negative impact on the company's performance. Quoted from Kontan.co.id, the weakening of the rupiah could weigh on ANTM's performance. Because, in the second quarter of 2018 ANTM suffered a foreign exchange loss of IDR 173 billion. This figure jumped 122% compared to the previous quarter. One of the reasons for this is that 72% of ANTM's debt up to the first semester is denominated in US dollars, which is sensitive to the volatility of the rupiah exchange rate. Based on agency theory, managerial ownership and debt covenants are considered to be able to influence the demand for conservative financial statements. So this study aims to explain and analyze the effect of debt covenants and managerial ownership on conservatism in mining companies listed on the IDX in 2015-2019. The sample used in this study was 55 by testing using multiple linear regression which was processed using SPSS version 25 software. The results of the research showed that debt covenants as measured by performance covenants had no effect, while managerial ownership had a positive effect on conservatism.